Landscapes of Lifelong Learning Policies across Europe Comparative Case Studies - Benasso, Sebastiano; Bouillet, Dejana; Neves, Tiago; Parreira do Amaral, Marcelo (Palgrave Studies in Adult Education and Lifelong Learning, 2022)
This open access book explores different landscapes of Lifelong Learning policies (LLP), producing case-based examinations of their institutional, discursive, and relational dimensions. Across Europe, young people develop their life courses amidst diverse living conditions and are confronted with a variety of institutional and structural arrangements that impact on their opportunities in education and labour. Considering the relevance of LLP in shaping those opportunities, the chapters draw from multi-level, mixed-methods research and offer original insights on the interplay of discourses and governance patterns in the processes of policy-making and deliverance. The book yields noteworthy insights into the widely differing realities across the European landscape, and also into the diverging ways young people deal with and actively participate in LLP.